Asymptomatic infection with Plasmodium falciparum and Plasmodium vivax in the Brazilian Amazon Basin: to treat or not to treat? - Mauro Shugiro Tada; Ricardo de Godoi Mattos Ferreira; Tony Hiroshi Katsuragawa; Rosimeire Cristina Dalla Martha; Joana D’Arc Neves Costa; Letusa Albrecht; Gerhard Wunderlich; Luiz Hildebrando Pereira da Silva (Memorias do Instituto Oswaldo Cruz, 2012)
In this study, we determined whether the treatment of asymptomatic parasites carriers (APCs), which are frequently found in the riverside localities of the Brazilian Amazon that are highly endemic for malaria, would decrease the local malaria incidence by decreasing the overall pool of parasites available to infect mosquitoes. In one village, the treatment of the 19 Plasmodium falciparum-infected APCs identified among the 270 residents led to a clear reduction (Z = -2.39, p = 0.017) in the incidence of clinical cases, suggesting that treatment of APCs is useful for controlling falciparum malaria. For vivax malaria, 120 APCs were identified among the 716 residents living in five villages. Comparing the monthly incidence of vivax malaria in two villages where the APCs were treated with the incidence in two villages where APCs were not treated yielded contradictory results and no clear differences in the incidence were observed (Z = -0.09, p = 0.933). Interestingly, a follow-up study showed that the frequency of clinical relapse in both the treated and untreated APCs was similar to the frequency seen in patients treated for primary clinical infections, thus indicating that vivax clinical immunity in the population is not species specific but only strain specific.